The resurrection as Christ's entry into his glory (Lk. 24:26) - Pieter G. R. de Villiers (Acta Theologica)
This essay discusses some apocalyptic perspectives on Luke’s portrayal of the resurrection as Christ’s entry into his glory (Lk. 24:26) in order to point out its mystical nature. After a discussion of some recent developments in research on Luke’s Christology and apocalyptic literature, the importance of glory in Early Jewish and Christian apocalypses is discussed. This is followed by an explanation of the glory motif in Luke 24:26, its place in Luke’s resurrection account in general and in the story of the disciples of Emmaus in particular. The essay then compares the mystical use of the glory motif in Luke 24:26 with Luke’s use of glory elsewhere in his writings. It concludes with general remarks about the mystical nature of the resurrection in Luke’s writings.